Detection of New Virulence Genes in mecA-positive Staphylococcus aureus Isolated From Clinical Samples: The First Report From Iran. Issue 6 (November 2017) - Eshaghi, Morteza; Bibalan, Meysam Hasannejad; Pournajaf, Abazar; Gholami, Mehrdad; Talebi, Malihe
Abstract : Background: Methicillin-resistant Staphylococcus aureus (MRSA) has become a main clinical and epidemiological concern for the past decades. These isolates have spread worldwide, causing health care– and community-associated infections. The aim of the present work was the determination of antibiotic resistance profile and simultaneous detection of psm-α and sasX genes in the clinical MRSA strains isolated from Tehran—the first report from Iran. Methods: This descriptive study was performed on hospitalized patients during August to February 2015. Antibiotic susceptibility test for all S. aureus isolates was conducted on Mueller-Hinton agar. The presence of mecA, sasX, and psm genes was detected by multiplex polymerase chain reaction method. Results: Of 153 S. aureus, 79 (51.6%) of the strains carried the mecA gene. Molecular analysis of mecA -positive S. aureus showed that the prevalence of sasX and psm genes was 13.9% (11/79) and 7.6% (6/79), respectively. Conclusions: This is the first report of sasX and psm genes among S. aureus isolates from Iran. Phenol-soluble modulins have recently appeared as a novel toxin family describing the virulence potential of vastly aggressive S. aureus . Current understanding is needed on S. aureus surface protein-encoding gene sasX, which plays a vital role in colonization and pathogenesis of MRSA. Abstract : This study is the first report from Iran about the prevalence of sasX virulence gene in clinical samples.